2020
DOI: 10.1002/jor.24887
|View full text |Cite
|
Sign up to set email alerts
|

Cemented short‐stem total hip arthroplasty: Characteristics of line‐to‐line versus undersized cementing techniques using a validated CT‐based finite element analysis

Abstract: Short stems are becoming increasingly popular in total hip arthroplasty as they preserve the bone stock and simplify the implantation process. Short stems are advised mainly for patients with good bone stock. The clinical use of short stems could be enlarged to patients with poor bone stock if a cemented alternative would be available. Therefore, this study aimed to quantify the mechanical performance of a cemented short stem and to compare the “undersized” cementing strategy (stem one size smaller than the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Using prototypes of the optimys stem fabricated using polished steel (Figure 12 ), a recent in vitro biomechanical study demonstrated that the concept of a line-to-line cementation technique could be further pursued for the development of a cemented short stem in THA[ 60 ]. This finding was confirmed in a validated, computed tomography-based, finite element analysis performed by Azari et al [ 61 ] that quantified the mechanical performance of this short stem design. The results suggested that cemented short stems are a promising alternative for use in osteoporotic bone and may, therefore, further expand the range of indications in the future.…”
Section: Indicationssupporting
confidence: 68%
“…Using prototypes of the optimys stem fabricated using polished steel (Figure 12 ), a recent in vitro biomechanical study demonstrated that the concept of a line-to-line cementation technique could be further pursued for the development of a cemented short stem in THA[ 60 ]. This finding was confirmed in a validated, computed tomography-based, finite element analysis performed by Azari et al [ 61 ] that quantified the mechanical performance of this short stem design. The results suggested that cemented short stems are a promising alternative for use in osteoporotic bone and may, therefore, further expand the range of indications in the future.…”
Section: Indicationssupporting
confidence: 68%
“…To date, there have been no new-generation cemented short stems used clinically. The utilization of the line-to-line technique in the development of cemented short stems may present a promising alternative for the treatment of osteoporotic bone conditions (Azari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%